Importance of Logic in Law - Fernández Procel, Karla (2019)
Since antiquity there is evidence of an interest for legal reasoning. With the emergence of logic in Greece, between the sixth and fifth centuries BC and the Eleatic school, whose main representative was Parmenides, it was established one of the axioms of this science: the law of identity. However, with few advances after Aristotle, especially during the Middle Ages, and despite the interest that Scholasticism shows in the use of this rational tool, innovations in logic remained stagnant for a long time. It is from the end of the nineteenth century and the beginning of the twentieth, with the emergence of symbolic logic, developed by thinkers such as Frege, Peano, Russell and Whitehead, that this discipline acquires a new impulse that is deployed to the present. The Legal Logic has based and identified basic principles that are necessarily linked to the application of Law. Finally, it is concluded that the interrelation between Logic and Law provides the latter with an adjusted interpretation of the norm, ensures a good process, and serves as a tool in making decisions. KEY WORDS: legal logic, judicial decision, reasoning, limits, Law. JEL CODE: A14, D23